Persistent Low-Risk and High-Risk Human Papillomavirus Infections of the Uterine Cervix in HIV-Negative and HIV-Positive Women - Adebamowo, Sally N.; Olawande, Oluwatoyosi; Famooto, Ayotunde; Dareng, Eileen O.; Offiong, Richard; Adebamowo, Clement A.; , for the H3Africa ACCME Research Group (Frontiers in Public Health, 2017)
Background The prevalence, persistence, and multiplicity of human papillomavirus (HPV) infection appears different comparing HIV-positive to HIV-negative women. In this study, we examined prevalent, persistent, and multiple low- and high-risk cervical HPV infections in HIV-negative and HIV-positive women. Methods We studied 1,020 women involved in a study of HPV infection using SPF25/LiPA10. Two study visits were scheduled, at enrollment and 6 months afterward. At each study visit, research nurses used a cervical brush to collect samples of exfoliated cervical cells from the cervical os, from all the study participants. Exact logistic regression models were used to estimate associations between HIV and HPV infections. Results The mean (SD) age of the study participants was 38 (8) years, 56% were HIV-negative and 44% were HIV-positive. Among HIV-negative women at baseline, single low-risk HPV (lrHPV) infections occurred in 12%; multiple lrHPV in 2%; single high-risk human papillomavirus (hrHPV) infections in 9%, and multiple hrHPV infections in 2%. Single lrHPV infections were persistent in 6%, but there was no persistent multiple lrHPV infections. Single hrHPV infections were persistent in 4% while multiple hrHPV infections were persistent in 0.3%. Among HIV-positive women at baseline, single lrHPV infections occurred in 19%, multiple lrHPV in 6%, single hrHPV infections in 17%, and multiple hrHPV infections occurred in 12%. Single lrHPV infections were persistent in 9%, multiple lrHPV infections in 0.6%, single hrHPV infections in 13%, while multiple hrHPV were persistent in 3%. Prevalent, persistent, and multiple infections were more common in HIV-positive women, compared to HIV-negative women. In multivariate models adjusted for age, marital status, socioeconomic status, age at sexual initiation, and douching, the odds ratios comparing HIV-positive to HIV-negative women, were 2.09 (95% CI 1.47–2.97, p < 0.001) for prevalent lrHPV, 1.26 (95% CI 0.66–2.40, p 0.47) for persistent lrHPV infections, 3.38 (95% CI 2.34–4.87, p < 0.001) for prevalent hrHPV, and 4.49 (95% CI 2.26–8.91, p < 0.001) for persistent hrHPV infections. Conclusion HIV infection was associated with higher prevalence of lrHPV, hrHPV, and persistence hrHPV infections, but not persistent lrHPV infections.